Association of long‐term hyperglycaemia and insulin resistance with brain atrophy and cognitive decline: A longitudinal cohort study. Issue 4 (10th January 2023) - Yu, Ji Hee; Kim, Regina E. Y.; Park, So Young; Lee, Da Young; Cho, Hyun Joo; Kim, Nam Hoon; Yoo, Hye Jin; Seo, Ji A; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Shin, Chol; et al.
Abstract: Aim: To investigate the longitudinal changes in brain volume and cognitive function associated with diabetes at midlife, and to examine whether long‐term hyperglycaemia, insulin resistance or secretory function is associated with brain atrophy and cognitive decline. Materials and Methods: We used data from 2377 participants with both baseline and 4‐year follow‐up brain magnetic resonance images and neuropsychological measures from the Ansan cohort of the Korean Genome Epidemiology Study. Time‐weighted mean glycaemic values were calculated using all measurements over an average duration of 10.6 years from cohort initiation to baseline visits. Results: Type 2 diabetes was associated with greater white matter volume reduction (adjusted volume difference = −1.96 ml, 95% CI: −3.73, −0.18) and executive function decline (adjusted Z score difference = −0.14, 95% CI: −0.23, −0.05) during the follow‐up period of 4.2 years. Decline of verbal and visual memory or verbal fluency was not associated with diabetes. Greater executive function decline was associated with higher time‐weighted mean HbA1c level over the preceding 10.6 years ( P  < .001), but not with insulin resistance markers in the diabetes group. Participants with diabetes, whose time‐weighted average HbA1c level was maintained above 6.5% over the previous decade, showed greater decline in executive function and global cognition than the normal glucose group. Conclusions: Long‐term hyperglycaemia was a major independent factor associated with rapid cognitive decline in middle‐aged adults with diabetes. Maintaining ideal glucose levels in diabetes at midlife might prevent later rapid cognitive decline.